Empirical methods in business location research. Issue 1 (1st January 2021) - Carpenter, Craig Wesley; Van Sandt, Anders; Loveridge, Scott
ABSTRACT: A frequent theme in regional science is exploring the determinants of business establishment locations. We briefly review the theoretical perspectives motivating several frameworks underpinning locational determinant analyses. We summarize and review trade-offs involved in established and emerging econometric techniques that researchers use to analyse locational determinants. We conclude with opportunities for future research, including understudied frameworks, potential data sources and methodological developments.